Peran Orang Tua dalam Menanamkan Pendidikan Agama Islam di Era Digital - Masud, Moh. Ali; Fitria, Mulajimatul; Slamet, Slamet (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
The digital era brings significant changes in various aspects of life, including in parenting patterns and Islamic religious education for children. Parents have a major role in instilling Islamic values ​​as provisions for children in facing increasingly rapid technological developments. This study aims to analyze the role of parents in instilling Islamic religious education in the digital era and the challenges faced. This study uses a qualitative method with a descriptive approach. Data were collected through literature studies from various related sources, such as journals, books, and previous studies. The results of the study show that parents face various challenges in guiding children, such as exposure to negative content, cyberbullying, social media addiction, and declining interest in religious learning. To overcome these challenges, parents need to implement effective strategies, such as providing role models, familiarizing children with Islamic worship and morals, utilizing technology wisely, and carrying out ongoing supervision and guidance. With a balanced approach between conventional methods and modern technology, parents can guide children to maintain strong Islamic values ​​amidst the rapid flow of digital information. Therefore, increasing digital literacy for parents is a crucial aspect in ensuring Islamic religious education remains relevant and effective in the modern era.